2022
DOI: 10.1001/jamanetworkopen.2022.45596
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune-Related Adverse Events, Hospitalization, and Therapy Resumption With Survival Among Patients With Metastatic Melanoma Receiving Single-Agent or Combination Immunotherapy

Abstract: ImportanceImmune-related adverse events (irAEs) due to immune checkpoint blockade (ICB) have been shown to be positively associated with survival. Among patients with metastatic melanoma, evidence supporting this association has been conflicting, while ipilimumab-nivolumab combination ICB has been examined only in small clinical cohorts.ObjectiveTo examine the association between irAEs and survival among patients with metastatic melanoma, in particular for those receiving combination ICB.Design, Setting, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…This is an important reason to support the idea of re-using this treatment despite the toxicity. In a study explained earlier [ 53 ], the patients under rechallenge had a better OS than those who were not retreated after toxicity. An Italian work [ 55 ] carried out a systematic review of studies that reported the efficacy and safety of ICI rechallenge.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is an important reason to support the idea of re-using this treatment despite the toxicity. In a study explained earlier [ 53 ], the patients under rechallenge had a better OS than those who were not retreated after toxicity. An Italian work [ 55 ] carried out a systematic review of studies that reported the efficacy and safety of ICI rechallenge.…”
Section: Discussionmentioning
confidence: 98%
“…A recent retrospective study published in December 2022 [ 53 ] examined the association between irAEs and survival in metastatic melanoma patients and included a sub-analysis of overall survival (OS) in patients hospitalized for an irAE and then resumed ICI treatment. They defined resumption after an irAE as a patient who received ≥1 cycle of ICI after withholding ICI for irAEs.…”
Section: Description Of the Evidencementioning
confidence: 99%
“…The longer TFS seen for patients receiving combination nivolumab-ipilimumab therapy may be associated with a more durable initial period of disease control, permitting SSAC therapy withdrawal, or the development of treatment-limiting adverse events followed by a treatment-free interval. These immune-related adverse events have been shown to be an established treatment biomarker of the likely benefit from ICI therapy . However, the subset of patients included in the combination nivolumab-ipilimumab cohort also had a lower ECOG status, were younger, and were more likely to be BRAF V600E variant positive, all of which may have been associated with the trend toward improved TFS in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous analyses had further stratified TFS based on the presence of immune-related adverse events into TFS with toxic effects and TFS without toxic effects, which could not be replicated in this cohort. Therefore, it is possible that, although patients receiving combination nivolumab-ipilimumab experienced longer TFS, a greater portion of this time was spent with additional toxic effects, as was seen in previous clinical trial analyses . Another limitation is the lack of information regarding choice of SSAC therapy for patients included in this analysis, which may have provided additional context for interpreting differences in duration receiving SSAC therapy seen in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation